2021
DOI: 10.1002/jha2.369
|View full text |Cite
|
Sign up to set email alerts
|

Transient left ventricular dysfunction following chimeric antigen receptor T‐cell‐mediated encephalopathy: A form of stress cardiomyopathy

Abstract: Chimeric antigen receptor (CAR) T-cell therapy represents a new strategy in treating lymphoid malignancies, such as relapsed-refractory diffuse large B-cell lymphoma (DLBCL). Several toxicities including cytokine release syndrome (CRS), neurotoxicity, and cardiovascular toxicity have been linked to CAR T-cell therapy. Transient impairment in left ventricular systolic function is described after CAR-T, however, the mechanism remains poorly understood. This paper reports the clinical presentation and outcome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In contrast, the proportion of B cells did not differ significantly within subgroups, thereby indicating prolonged inflammation duration during the progressive phase of the disease [32]. Interestingly, a review of past case studies revealed that patients treated with CAR-T in oncology therapy show manifestations similar to those of stress cardiomyopathy [33], thus suggesting that surface T cells may be involved in the development of stress cardiomyopathy and that early treatment with immunosuppressive agents does improve the prognosis of stress cardiomyopathy [34]. These findings may suggest a unique role of immunity in stress cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the proportion of B cells did not differ significantly within subgroups, thereby indicating prolonged inflammation duration during the progressive phase of the disease [32]. Interestingly, a review of past case studies revealed that patients treated with CAR-T in oncology therapy show manifestations similar to those of stress cardiomyopathy [33], thus suggesting that surface T cells may be involved in the development of stress cardiomyopathy and that early treatment with immunosuppressive agents does improve the prognosis of stress cardiomyopathy [34]. These findings may suggest a unique role of immunity in stress cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%